Image analysis of Bacillus thuringiensis - Dickason, Gregory John (Centre for Bioprocess Engineering Research, 2016)
This thesis concerns the development of a method to quantify the morphology of the bacterium Bacillus thuringiensis, and to automatically count the bacteria. The need to quantify the bacterial morphology arose out of the possibility of controlling a fermentation based on the morphology of the observed bacteria. Automatic counting of bacteria was considered necessary to reduce the inaccuracies that resulted in manual counts performed by different people. Bacillus thuringiensis is a spore forming, gram-positive bacterium, which produces both intracellular spores and insecticidal protein crystals. The production of the insecticidal protein crystal makes Bacillus thuringiensis important as a producer of biological insecticides. Automatic counting was developed in a Thoma counting chamber (Webber Scientific) at 200x magnification under dark field illumination. It was found that at this magnification the problem of out of focus cells was eliminated. The use of a thick coverslip, which reduces variability in slide preparation, was also possible at 200xmagnification as the focal depth of the 20x objective lens was considerably larger than the 1 00x objective lens and thus the 20x objective lens could focus through the thick coverslip (20x objective lens with 1 Ox magnification in eyepiece = 200xmagnification). An automatic algorithm to acquire images was developed and 5images per sample were acquired. Processing of the images involved automatically thresholding and then counting the number of bright objects in the image. Processing was thus rapid and the processing of the five images took no more than a few seconds. Results showed that the correlation between the automatic and manual counts was good and that the use of a thick coverslip reduced variability in slide preparation. It was shown that the manual -counting procedure, which necessarily used a thin coverslip at 1000x magnification, underestimated the volume of the Thoma counting chamber. This was a result of warping in the thin coverslip.